O rural ritualizado: nas asas do gavião tecendo novos olhares para o rural contemporâneo - Coghetto, Franciele (2019)
This thesis is the result of the observation of the recurrent use of rural space by groups linked to New Age, which have been using such space for their spiritual and religious practices. Considering the multiple functions that rural space has had in the contemporary world, in this study we recognize the importance of the notion of multifunctionality to weave elucubrations that help understand these resemantizations, whose core device is the praising of nature. In an attempt to clarify how these new views are engendered, this study had the Choupana do Gavião group as its empirical focus through an ethnographic essay done in the Upper Uruguay Rio Grande do Sul Region. Based on the analysis of the trajectories of the group and its members, along with the immersion in their rituals, the ethnographic findings point out that spirituality joined with agroecology indicates the unveiling of a phenomenon relevant to the texture of new ways of thinking and conceiving the rural.